2022
DOI: 10.1186/s12864-022-08578-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel key regulatory lncRNAs in gastric adenocarcinoma

Abstract: Background Stomach adenocarcinoma (STAD) is one of the most common and deadly cancers worldwide. Recent evidence has demonstrated that dysregulation of long noncoding RNAs (lncRNA) is associated with different hallmarks of cancer. lncRNAs also were suggested as novel promising biomarkers for cancer diagnosis and prognosis. Despite these previous investigations, the expression pattern, diagnostic role, and hallmark association of lncRNAs in STAD remain unclear. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Furthermore, the vital function and mechanism of lncRNAs in tumorigenesis and progression have been recognized with the help of clinical bioinformatics analysis combined with functional research. Previous studies had identified the oncogenic role of NALT1 in GC tissues and related to poor patients’ prognosis [ 4 , 5 ]. Very little information is available about the molecular mechanisms of NALT1 in CRC carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the vital function and mechanism of lncRNAs in tumorigenesis and progression have been recognized with the help of clinical bioinformatics analysis combined with functional research. Previous studies had identified the oncogenic role of NALT1 in GC tissues and related to poor patients’ prognosis [ 4 , 5 ]. Very little information is available about the molecular mechanisms of NALT1 in CRC carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…had identified the oncogenic role of NALT1 GC tissues and related to poor patients' prognosis [4,5]. Very little information is available about the molecular mechanisms of NALT1 in CRC carcinogenesis.…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the vital function and mechanism of lncRNAs in tumorigenesis and progression have been recognized with the help of clinical bioinformatics analysis combined with functional research. Previous studies had identi ed the oncogenic role of NALT1 in GC tissues and related with poor patients' prognosis 4,5 . Very little information is available about the molecular mechanisms of NALT1 in CRC carcinogenesis.…”
Section: Schematic Diagram 4 Discussionmentioning
confidence: 99%
“…LncRNA NOTCH1 associated lncRNA in T cell acute lymphoblastic leukemia 1 (NALT1) acts as a regulator to be implicated in the development of gastric cancer (GC) 4 . Additionally, dysregulated NALT1 expression was found to be associated with overall survival (OS) in stomach adenocarcinoma (STAD) and might facilitate cancer cell proliferation 5 . Dysregulaton of lncRNAs has been commonly found in CRC, which may be involved in CRC cell growth, migration, and metastasis 6,7,8 .…”
Section: Introductionmentioning
confidence: 99%